Editorial - Organizing & Evaluation Committee (Brazilian Journal of Production Engineering, 2026)
The VI Symposium on Production Engineering, promoted by the Postgraduate Program in Production Engineering (PPGEP) and the undergraduate program in Production Engineering at UFCAT, is a national event encompassing teaching, research, outreach, and culture. Its target audience includes postgraduate and undergraduate students, professors, researchers, engineers, and other professionals working in Production Engineering and related fields. The event took place on September 25th, 26th, and 27th, 2024, at the Federal University of Catalão, with the theme "Technologies and Integrated Systems in Production Planning and Control". Thus, the main objective was to explore the integration of technologies and systems into Production Planning and Control (PPC), fostering interaction between academia, industry, and society. This interaction occurred through the event's activities, such as lectures, short courses, roundtables, technical visits, a space for opportunities with companies, challenges, a solidarity action, and a cultural event. All these activities, taken together, promoted research, teaching, innovation, outreach, and culture.